Factors associated with long turnaround time for early infant diagnosis of HIV in Myanmar - Soe Thiha; Hemant Deepak Shewade; Sairu Philip; Thet Ko Aung; Nang Thu Thu Kyaw; Myo Minn Oo; Khine Wut Yee Kyaw; May Wint War; Htun Nyunt Oo (Taylor & Francis Group, 2017)
Background: A previous review of early infant diagnosis (EID) using polymerase chain reaction technology (PCR) under integrated HIV care (IHC) program in Myanmar revealed a low uptake of timely (within 6 to 8 weeks of babies' age) EID and a long turnaround time (TAT) of receiving results. Objective: This study aimed to determine the proportion and factors associated with the composite outcome of a long TAT (≥7 weeks; from sample collection to receipt of result by mother) or nonreceipt of result among HIV-exposed babies whose blood samples were collected for PCR at <9 months of age under the IHC program, Myanmar (2013-15). Methods: Cohort study involving record review of routinely collected data. A predictive Poisson regression model with robust variance estimates was fitted for risk factors of long TAT or nonreceipt of result. Results: Blood samples of 1 000 babies were collected; among them, long TAT or nonreceipt of results was seen in 690 (69%), and this was more than 50% across all subgroups. Babies with a mother's CD4 count of 100-350 cells/mm3 at enrollment [adjusted RR (0.95 confidence intervals, CI): 0.8 (0.7, 0.9)] had a 20% lower risk of long TAT or nonreceipt of results when compared with ≥350 cells/mm3. Distance between ART center and PCR facility ≥105 km [adjusted RR (0.95 CI): 1.2 (1.1, 1.4)], when compared with <105 km, was associated with 20% higher risk of long TAT or nonreceipt of results. Conclusions: The proportion of babies with long TAT or nonreceipt of result by the mother was high. Point-of-care testing for EID may reduce TAT/nonreceipt of results by the mother. Health system, laboratory, and logistic factors such as sample transportation, laboratory procedures, and result dispatching associated with long TAT should be further explored.